The Theory of Tauhid-Based Islamic Education in the Thought of Al-Ghazali and Ibn Khaldun - Chotami Fajrin Lowchin; Abi Thohir Muhammad Al Kautsar Rohman; Rizal Setiawan Rohman; Ahmad Sudarmanto Rohman; Siti Mahmudah Noorhayati Rohman (INTIFA: Journal of Education and Language, 2026)
This study aims to analyze the theory of tauhid-based Islamic education from the perspectives of Al-Ghazali and Ibn Khaldun, as well as to examine its relevance to contemporary Islamic education. This research employs a qualitative approach with a library research design, drawing on primary sources from the major works of both scholars and supported by relevant academic literature. Data were collected through documentation techniques and analyzed using content analysis and a comparative approach. The findings reveal that tauhid functions as a philosophical foundation encompassing ontological, epistemological, and axiological dimensions in Islamic education. In Al-Ghazali’s perspective, education emphasizes spiritual purification and the integration of knowledge and action as a path toward closeness to Allah. Meanwhile, Ibn Khaldun highlights the development of religious and intellectual malakah (habitual dispositions) as the basis for the formation of a civilized society. Despite their different emphases, both scholars consistently position tauhid as an integrative principle that unifies faith, knowledge, and action. This study concludes that the synthesis of Al-Ghazali’s and Ibn Khaldun’s thoughts produces a holistic, integrative, and transformative paradigm of tauhid-based Islamic education. This paradigm is highly relevant in addressing contemporary challenges such as secularization and moral crises by orienting education toward the formation of the insān kāmil (perfect human being), who is balanced in spiritual, intellectual, and social dimensions. Therefore, tauhid-based education offers a strategic contribution to the development of a sustainable and value-oriented Islamic education system.